Determinasi Niat Nasabah dalam Memilih Produk Kredit di Banco Nacional de Comércio Timor-Leste: Peran Norma Subjektif dan Sikap dengan Moderasi Faktor Demografi - Bere, Marcos Ulan; Lutfi, Lutfi (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
The study aims to analyze the factors influencing customer intentions to choose credit products at Banco Nacional de Comércio Timor Leste, focusing on subjective norms, attitudes, and customer demographic factors. The study used a quantitative approach with the SEM-PLS method on 120 credit customers selected through a purposive sampling technique. The results showed that subjective norms and attitudes significantly influenced customer intentions to choose credit products. Marital status was also proven to have a significant influence on customer intentions and was able to strengthen the influence of subjective norms on the intention to choose credit products, but did not moderate the influence of attitudes on intentions. Education, gender, and age were found to have no significant influence on the intention to choose credit products. The findings of this study can be used as strategic considerations for banks and banking authorities in formulating more effective and efficient promotional strategies, credit education, and financial behavior.